2016
DOI: 10.1002/uog.15897
|View full text |Cite
|
Sign up to set email alerts
|

Sphenofrontal distance on three-dimensional ultrasound in euploid and trisomy-21 fetuses at 16-24 weeks' gestation

Abstract: Objective To compare the distance between the sphenoid and frontal bones on three-dimensional (3D)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
1
1
3
Order By: Relevance
“…Cossellu et al . examined the SFD antenatally and found it was < 5 th centile in more than 90% of pregnancies with trisomy 21. This is in contrast with our study, in which only 25% of the trisomy‐21 fetuses had a SFD < 5 th centile.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Cossellu et al . examined the SFD antenatally and found it was < 5 th centile in more than 90% of pregnancies with trisomy 21. This is in contrast with our study, in which only 25% of the trisomy‐21 fetuses had a SFD < 5 th centile.…”
Section: Discussioncontrasting
confidence: 99%
“…In a recent publication, Cossellu et al . introduced the sphenofrontal distance (SFD) in screening for trisomy 21. They used three‐dimensional (3D) ultrasound volumes acquired between 16 and 24 weeks' gestation for 30 fetuses with trisomy 21 and 80 euploid fetuses and found that the SFD was < 5 th and < 1 st centile in 97% and 90% of aneuploid cases, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…La técnica de realización de las mediciones es reproducible en personal entrenado. En esta investigación las mediciones estuvieron acorde a parámetros de otros autores (1,3,12).…”
Section: Métodosunclassified
“…En el desarrollo embriológico el primordio facial aparece en la cuarta semana de gestación alrededor del gran estomodeo primordial, como 5 prominencias mesenquimales (2,3). Durante la semana 8, centros iniciales de osificación de los huesos nasales aparecen en la membrana que cubre la cápsula nasal cartilaginosa (2), pero es ya avanzada la edad gestacional (EG) que diversos autores se han dedicado a evaluar el perfil fetal en busca de alteraciones asociadas con el síndrome de Down (1,4).…”
Section: Introductionunclassified
See 1 more Smart Citation